Trend in Language, Ethnic and Learning: Bibliometric Litterature Review - Astuty Astuty; Herpindo Herpindo; Farikah Farikah; Miftahula Rizkqin Nikmatullah (Universitas Cokroaminoto Palopo, 2025)
The aim of this research is to conduct a thorough bibliometric literature review of the complex and multifaceted relationships between language, ethnicity, and learning, using sophisticated computational techniques to map and analyze academic scholarship across diverse interdisciplinary domains. Using modern data mining and network analysis approaches, the researchers deconstructed established educational research paradigms by carefully examining publication trends, citation networks, and topic clusters. The complete investigation indicated that linguistic and ethnic variety are not educational impediments, but rather rich reservoirs of cultural information and cognitive flexibility, calling into question traditional deficit-oriented theories of academic comprehension. The findings revealed that bilingual and multilingual learners had significantly improved cognitive capacities, such as superior executive functioning, metacognitive skills, and cross-cultural problem-solving abilities, which go beyond typical monolingual learning frameworks. The study revealed significant regional discrepancies in knowledge production, with academic work mostly centered in North American and European institutional environments, emphasizing systemic imbalances in global knowledge formation. By repositioning linguistic and cultural diversity as fundamental intellectual strengths rather than limitations, the study offers transformative insights into developing more inclusive, equitable, and dynamic educational strategies capable of effectively responding to the complexities of an increasingly interconnected global academic and technological landscape. The findings not only challenge existing educational paradigms, but also offer a nuanced, comprehensive framework for understanding cognitive potential across diverse linguistic and cultural backgrounds, eventually advocating for a more holistic, culturally responsive approach to learning and academic